Sistem Informasi Administrasi Pembayaran Sumbangan Pembinaan Pendidikan (SPP) Berbasis Whatsapp Gateway - Ogi Saputra; Wifra Safitri (Rektorat Universitas Putra Indonesia YPTK Padang, 2022)
An information system is already a necessity by a school in running a better administrative system. The administrative information system using information technology with the help of computers is very helpful in the smooth operation of the school. One of the school's operations that is the principal for supporting operations is the payment of Educational Development Contributions (SPP). A more effective and efficient tuition payment procedure can streamline all school operational activities. This study aims to improve the administration of tuition payments with a whatsapp gateway-based system. This system can perform all SPP payment procedures on a mobile or mobile basis. The data processed in this study were sourced from the administration system for paying tuition fees at Mukomuko High School (SMA). The system uses PHP programming language tools and MySQL database. The result of this research is a computerized SPP payment administration system. So that the school administration can control tuition payments more effectively and efficiently. So that this system is very precise and fast in the administration of tuition payments and becomes a reference for other administrations in order to assist the administrative process and improve time efficiency and provide the right information.